2011
DOI: 10.2337/dc10-1177
|View full text |Cite
|
Sign up to set email alerts
|

High Rate of Regression From Micro-Macroalbuminuria to Normoalbuminuria in Children and Adolescents With Type 1 Diabetes Treated or Not With Enalapril

Abstract: OBJECTIVETo evaluate the frequency of normalization, the persistence of remission, and the impact on normalization of glycemic control and lipid profile, we analyzed data from a retrospective observational cohort study of type 1 diabetic children and adolescents with abnormal urinary albumin excretion (UAE).RESEARCH DESIGN AND METHODSAll diabetic children and adolescents (n = 41) who had persistent abnormal UAE in the period of 1984 to 2008 and followed up until 2009 (follow-up duration = 13.1 ± 6.2 years) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 25 publications
4
33
2
Order By: Relevance
“…In the present survey, regression rate of persistent microalbuminuria to intermittent microalbuminuria or normoalbuminuria without ACE inhibitor treatment was estimated at 71.2%. This percentage is comparable to a recently published, small study, where 14 out of 17 patients (82% of patients) who had never received ACE inhibitors underwent spontaneous remission during a follow-up period of 13.1G6.2 years (36). Many studies have examined risk factors including glycaemic control, diabetes duration, sex, smoking, hypertension and disturbed lipid metabolism to determine and predict diabetic nephropathy (1,2,3,4,5,6,35,37).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In the present survey, regression rate of persistent microalbuminuria to intermittent microalbuminuria or normoalbuminuria without ACE inhibitor treatment was estimated at 71.2%. This percentage is comparable to a recently published, small study, where 14 out of 17 patients (82% of patients) who had never received ACE inhibitors underwent spontaneous remission during a follow-up period of 13.1G6.2 years (36). Many studies have examined risk factors including glycaemic control, diabetes duration, sex, smoking, hypertension and disturbed lipid metabolism to determine and predict diabetic nephropathy (1,2,3,4,5,6,35,37).…”
Section: Discussionsupporting
confidence: 62%
“…Furthermore, other studies showed that abnormal lipid profiles are risk factors for the development of microalbuminuria (36,39). Especially, lower HDL-cholesterol levels are present in patients with type 1 diabetes and microalbuminuria (36). However, and in contrast to those studies, we did not observe such an effect.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…Although, renal failure in diabetic kidney disease usually occurs after many years of disease, the early stages of diabetic kidney disease characterized by increased albuminuria are observed also in the paediatric population [110][111][112][113]. In adolescents kidney damage in T1DM is directly related to elevated BP values, and effective antihypertensive treatment slows the progression of kidney damage [114].…”
Section: Pathogenesis Of Hypertension In Children With Diabetesmentioning
confidence: 99%